An Explanation of International Migration: A Case Study of Pakistan - Haris, Seema; Mahmood, Dr. Khalid (Al-Amīr Research Journal for Islamic Studies, 2024)
International migration poses significant challenges, especially for developing countries. This study examines the economic, socio-political, and demographic drivers of international migration, with a specific focus on Pakistan, to determine which factors exert the strongest influence. Primary data were gathered from domestic and foreign participants to understand their motivations for migration. The findings indicate that, among economic, demographic, and socio-political factors, the latter is the most influential in driving international migration from Pakistan. Key push factors include corruption and family responsibilities, while major pull factors involve access to quality education and higher wages. To retain its young workforce, Pakistan must foster an environment with improved labor market opportunities and instill confidence in its citizens. Keywords: International Migration, Socio-Political Factors, Economic Drivers, Demographic Factors, Pakistan Migration Trends.